2022
DOI: 10.7554/elife.74819
|View full text |Cite
|
Sign up to set email alerts
|

Stable antibiotic resistance and rapid human adaptation in livestock-associated MRSA

Abstract: Mobile genetic elements (MGEs) are agents of horizontal gene transfer in bacteria, but can also be vertically inherited by daughter cells. Establishing the dynamics that led to contemporary patterns of MGEs in bacterial genomes is central to predicting the emergence and evolution of novel and resistant pathogens. Methicillin-resistant Staphylococcus aureus (MRSA) clonal-complex (CC) 398 is the dominant MRSA in European livestock and a growing cause of human infections. Previous studies have identified three ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 78 publications
1
33
0
Order By: Relevance
“…Although the isolation rate of MRSA was low in our isolates, other isolates showed significant resistance to penicillins. Therefore, the prevalence of LA‐MRSA might be much higher in the future because of selective pressures (Matuszewska et al., 2022 ). Because LA‐MRSA might function as a reservoir for MRSA that can infect people (Fessler et al., 2011 ; Li et al., 2017b ; Loncaric et al., 2013 ; Loncaric & Künzel, 2013 ), we suggest regular longitudinal surveillance of MRSA in livestock animals, especially pigs and chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Although the isolation rate of MRSA was low in our isolates, other isolates showed significant resistance to penicillins. Therefore, the prevalence of LA‐MRSA might be much higher in the future because of selective pressures (Matuszewska et al., 2022 ). Because LA‐MRSA might function as a reservoir for MRSA that can infect people (Fessler et al., 2011 ; Li et al., 2017b ; Loncaric et al., 2013 ; Loncaric & Künzel, 2013 ), we suggest regular longitudinal surveillance of MRSA in livestock animals, especially pigs and chickens.…”
Section: Discussionmentioning
confidence: 99%
“…All strains harboured SCCmec subtype Vc(5C2&5). This was the dominant SCCmec subtype in LA-MRSA CC398 in two studies including sequences from several European countries [54,55]. SCCmec Vc(5C2&5) is known to carry heavy metal resistance gene crzC and tetracycline resistance gene tet(K) in addition to mecA.…”
Section: Discussionmentioning
confidence: 99%
“…SCCmec Vc(5C2&5) is known to carry heavy metal resistance gene crzC and tetracycline resistance gene tet(K) in addition to mecA. It has been suggested that the use of zinc oxide in pig production may have favoured the selection of strains carrying SCCmec Vc [55]. The effects of an EU-wide ban on zinc oxide in pig husbandry as of 26 June 2022 on the prevalence of LA-MRSA CC398 remain to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…The major virulence factors and AMR genes are localized on mobile genetic elements (MGEs). A recent report suggested that CC398, the dominant livestock-associated MRSA in Europe, rapidly adapted to cause human infections [ 25 ]. Due to the clonal expansion, S .…”
Section: Introductionmentioning
confidence: 99%
“…The major virulence factors and AMR genes are localized on mobile genetic elements (MGEs). A recent report suggested that CC398, the dominant livestock-associated MRSA in Europe, rapidly adapted to cause human infections [25]. Due to the clonal expansion, S. aureus strains belonging to the same CC have specific virulence gene signatures [26,27] and restriction-modification systems that reduce HGT between different S. aureus lineages [28,29].…”
Section: Introductionmentioning
confidence: 99%